TECHNOLOGY BUSINESS INCUBATION CENTRE IMPACTS ON STARTUP COMPANIES, COIMBATORE (INCUBATE PERSPECTIVE) - K. Karthikeyan; K. Ramya (Proceedings on Engineering Sciences, 2024)
This study focusing on the orientations of role of Technology supports towards the development of incubators, incubate development, problems and challenges of startup companies towards the acceptance of technology, various programes organized by incubators, benefits and achievement of incubates. Further to technology impacts on start up entrepreneurs’’ that the key internal variables contributing for technology adaptability, available technical relevant facilities of incubators, skill & knowledge transfer effectiveness. As interest in the part of future India with creativity of business, this study will helps to understand the gap between the existing incubation cell and the incubates requirements. According to articulated reviews, the research work is categories into 4 chapters. The model is also developed to attain the effective achieving the progression of phases. The questionnaire and interview schedule will be circulate among the 120 incubates in Coimbatore. Finally, 104 responded to the core study of this platform.